2021
DOI: 10.1093/hmg/ddab208
|View full text |Cite
|
Sign up to set email alerts
|

From APC to the genetics of hereditary and familial colon cancer syndromes

Abstract: Hereditary colorectal cancer syndromes attributable to high penetrance mutations represent 9–26% of young-onset colorectal cancer cases. The clinical significance of many of these mutations is understood well enough to be used in diagnostics and as an aid in patient care. However, despite the advances made in the field, a significant proportion of familial and early-onset cases remains molecularly uncharacterized and extensive work is still needed to fully understand the genetic nature of colorectal cancer sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 241 publications
1
18
0
Order By: Relevance
“…LS was by far the most frequent Mendelian CRC syndrome detected in our study, followed by FAP and MAP both at approximately 1% levels, that is, mutual ratios for LS, FAP, and MAP repeatedly shown in other studies of selected and unselected patients with CRC and in line with reported prevalences in general populations. 2,3,[5][6][7] Given their rarity, the absence of identified patients with PPAP, PJS, PTHS, and PJS is not surprising as the size of our cohort is limited. Also, as symptoms may present early in life, some patients with these conditions might have been diagnosed before adulthood by pediatricians and thus have escaped our study.…”
Section: Detected Genetic Variants and Variant Reclassificationmentioning
confidence: 98%
See 2 more Smart Citations
“…LS was by far the most frequent Mendelian CRC syndrome detected in our study, followed by FAP and MAP both at approximately 1% levels, that is, mutual ratios for LS, FAP, and MAP repeatedly shown in other studies of selected and unselected patients with CRC and in line with reported prevalences in general populations. 2,3,[5][6][7] Given their rarity, the absence of identified patients with PPAP, PJS, PTHS, and PJS is not surprising as the size of our cohort is limited. Also, as symptoms may present early in life, some patients with these conditions might have been diagnosed before adulthood by pediatricians and thus have escaped our study.…”
Section: Detected Genetic Variants and Variant Reclassificationmentioning
confidence: 98%
“…2,3 There are several less common Mendelian conditions that predispose to CRC, such as juvenile polyposis syndrome (JPS), PTEN hamartoma tumor syndrome (PHTS), Peutz-Jeghers syndrome (PJS), polymerase proofreading-associated polyposis (PPAP), and a handful additional more recently defined conditions. 3,4 Because DV may have prognostic, therapeutic, and prophylactic implications, screening for DV in selected patients with CRC and/or colorectal polyposis is routine in many health-care systems. In addition, identification of DV permits carrier testing and personalized health care for relatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenomatous polyposis coli (APC) gene is a tumour suppressor that inhibits the Wnt molecular pathway. It is known for its role in colorectal carcinogenesis and association with familial adenomatous polyposis (FAP) [107,108]. Its protein product can be detected by immunohistochemistry and has been recommended by WHO (2022) as an adjunct in the diagnostics of parathyroid carcinoma [12].…”
Section: Apc Proteinmentioning
confidence: 99%
“…Approximately 65% of CRC cases developed sporadically, without a family history or inherited genetic mutations predisposition, through multiple acquired somatic genomic and epigenetic alterations ( 3 , 4 ). Other cases are associated with heritable components such as family history (25%), hereditary cancer syndrome (5%), some known CRCs low-penetrance genetic variations (<1%), and other unknown inherited genomic alterations ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%